Digital Transformation Of Legal Education - Yuliya Kharitonova,; Larisa Sannikova, (Medicine, Law & Society, 2022)
Employers and practicing lawyers face the challenges of digitalisation in society. Many lack enough experience and skills to work with digital technologies. To increase the competitiveness of their graduates, universities have established advanced training programmes related to digital technologies and law; however, a common approach has yet to be found. The development and implementation of the proposed Framework for the Digital Competence of Lawyers will assist in solving novel problems in the field of legal education. This framework should include general digital competencies for all legal professions. The use of computer or virtual simulators, demo versions of popular digital platforms, and LegalTech hackathons within the educational process has been proposed to improve the digital skills of law students, which will allow examining the essence of ongoing processes and better acquire theoretical knowledge about new technologies.
Keywords: digital skills and competence, future technology, ICT, employability, digital competence of lawyers